Benefits of soy germ isoflavones in postmenopausal women with contraindication for conventional hormone replacement therapy - Nahas, E. P.; Nahas Neto, Jorge [UNESP]; De Luca, L.; Traiman, Paulo [UNESP]; Pontes, Anaglória [UNESP]; Dalben, Ivete [UNESP] (Elsevier B.V., 2004)
Objective: To evaluate the effects of isoflavones on vasomotor symptoms and blood lipids in postmenopausal women with contraindication for conventional hormone replacement therapy (HRT). Methods: This prospective, double-blind and placebo-controlled study included 50 postmenopausal women randomly divided into two groups: 25 women on soy germ isoflavones (60 mg per day, capsules) and 25 women on placebo. Inclusion criteria included: non-vegetarian, non-asian women whose last menstruation dated at least 12 months prior to the beginning of the study, With FSH > 40 mIU/ml, hot flushes and contraindication for HRT, not using tamoxifen or antibiotic and no disease of the gastrointestinal tract. For 6 months, the Kupperman menopausal index (KMI), the vaginal cytological maturation value (MV) and both hormonal and lipid profiles were assessed. The t-test and analysis of variance (ANOVA) were employed to compare the two groups. Results: In both groups, a decreased KI rate was observed. However, isoflavone was significantly superior to placebo in reducing hot flushes (44% versus 10%, respectively) (P < 0.05). After 6 months, the isoflavone group showed increased estradiol levels with unchanged FSH, LH, and vaginal cytology, and a reduction of 11.8% in LDL and an increase of 27.3% in HDL (P < 0.05). In the placebo group, just a reduction in MV was observed after 6 months (P < 0.05). Conclusions: Soy germ isoflavone exerted favorable effects on vasomotor symptoms and lipid profile, showing itself to be an interesting alternative therapy for the postmenopausal women with contraindication for conventional HRT. (C) 2003 Elsevier B.V.. All rights reserved.
Keywords: soy germ; isoflavone; menopause; hot flushes; lipid profile